The Iron(III) Thiocyanate Reaction Research History and Role in Chemical Analysis - de Berg, Kevin C. (History of Chemistry, 2019)
This Brief presents an historical investigation into the reaction between ferric ions and thiocyanate ions, which has been viewed in different ways throughout the last two centuries. Historically, the reaction was used in chemical analysis and to highlight the nature of chemical reactions, the laws of chemistry, models and theories of chemistry, chemical nomenclature, mathematics and data analysis, and instrumentation, which are important ingredients of what one might call the nature of chemistry. Using the history of the iron(III) thiocyanate reaction as a basis, the book's main objective is to explore how chemistry develops its own knowledge base; how it assesses the reliability of that base; and how some important tools of the trade have been brought to bear on a chemical reaction to achieve understanding, a worthwhile goal of any historical investigation.